A New Approach to Objective Evaluation of Human Visual Acuity - Hulewicz, Arkadiusz (Photonics Letters of Poland, 2014)
The subject matter of this paper refers to the objective visual acuity assessment methods using non-invasive measurements of visual evoked potentials (VEP) by means of special electrodes. An attempt was made to classify the data acquired enabling prompt and objective visual acuity evaluation. The purpose of the comparative measurements carried out in the paper was an attempt to calibrate the peak-to-peak VEP curve sections in the visual acuity function. Full Text: PDF References Cysewska-Sobusiak A., Hulewicz A., Grzybowski A., and Boltrukiewicz M., Obtaining and analysis of multifocal electroretinogram, Proc. of the 3rd European Medical and Biologi-cal Engineering Conference EMBEC 2005, Prague, Czech Republik, 20-25 November 2005, IFMBE Proceedings, vol. 11, pp. 1-6. Cysewska-Sobusiak A., Hulewicz A., Grzybowski A., and Boltrukiewicz M., Computer-assisted acquisition and statistical evaluation of multifocal Visual Evoked Potentials, Proc. of the IEEE International Conference on Virtual Environments, Human-Computer Interfaces, and Measurement Systems VECIMS 2006, La Coruna, Spain, pp. 149-153, 10-12 July 2006. Cysewska-Sobusiak A., Hulewicz A., and Grzybowski A., Application of visual evoked potentials to objective visual accuity assessment, Proc. of the 4th IET International Conference on Advances in Medical, Signal and Information Processing MEDSIP 2008, Santa Margherita Ligure, Italy, 14-16 July 2008. Heckenlively J. and Arden G. B., Principles and practice of clinical electrophysiology of vision, Mosby Year Book, 1991. Marmor M.F., Fulton A.B., Holder G.E., et al, ISCEV Standard for full-?eld clinical electroretinography, Documenta Ophthalmologica, vol. 118, pp. 69-77, February 2009. CrossRef Odom J. V., Bach M., Brigell M., et al., ISCEV standard for clinical visual evoked potentials, Documenta Ophthalmologica, vol. 120, 2010, pp. 111-119. CrossRef RETIport21: VEP, EOG, ERG Version 06.02, Instruction manual, Roland Consult, Germany, 2006. Smith G., Atchison D. A., The eye and visual optical instrument, Cambridge University Press, New York, 1997. CrossRef W. H. Ridder III, Methods of visual acuity determination with the spatial frequency sweep visual evoked potential, Documenta Ophthalmologica, vol. 109, pp. 239-247, November 2004. CrossRef